PERBANDINGAN METODE SINGLE EXPONENTIAL SMOOTHING DAN SINGLE MOVING AVERANGE DALAM PERAMALAN PERSEDIAAN BAHAN BAKU PADA ROEMAH DONAT LEZAT - Rahmadani, Sherly; Rizaldi, Rizaldi; Rahayu, Elly (J-Com (Journal of Computer), 2024)
Abstract: Roemah Donat Lezat carries out many sales transactions every day because the prices are affordable and the flavors and toppings are increasingly varied, this affects the supply of raw materials at Roemah Donat Lezat In managing raw material inventory, you must ensure sufficient inventory for sales, minimizing the time and costs required. So far, the owner of Roemah Donat Lezat does not have a method for anticipating how much supply of basic ingredients there is and only predicts without clear and precise calculations, therefore, sometimes Roemah Donat Lezat takes too little stock even though customer needs at the time the trend is increasing, causing no fulfilling customer requests and sometimes taking too much stock even though customer demand is decreasing resulting in losses, therefore Roemah Donat Lezat always finds it difficult and confused to estimate stock supplies for the following month To overcome the problems above, the author provides a solution using method comparison forecasting calculations, because it can provide a deeper and more detailed understanding of the advantages, weaknesses and relative performance of the two methods used to achieve a goal or solve a problem  The method used is Single Exponential Smoothing, which is forecasting used for the short term or usually only for the next month  Single Moving Average is a technique for calculating the average of a number from the latest actual values, updated as new values available for use in forecasting in subsequent periods.Keywords: single exponential smoothing-single moving average; forecasting; roemah donat lezat; raw materials; inventoryAbstrak: Roemah Donat Lezat setiap harinya banyak melakukan transaksi penjualan karena harga terjangkau dan semakin bervariasi rasa dan topping, hal ini mempengaruhi persediaan bahan baku jika ada di Roemah Donat Lezat  Dalam pengelolaan persediaan bahan baku harus memastikan persediaan jika cukup dalam penjualan, meminimalkan waktu dan biaya jika dibutuhkan.Selama ini pemilik Roemah Donat Lezat tidak memiliki metode dalam mengantisipasi seberapa banyak persediaan bahan-bahan pokok dan hanya memprediksi tanpa adanya perhitungan jika jelas dan tepat maka dari itu, terkadang Roemah Donat Lezat terlalu sedikit mengambil stok padahal kebutuhan pelanggan waktu trend itu sedang meningkat menyebabkan tidak terpenuhinya permintaan pelanggan dan kadang-kadang juga cenderung mengambil terlalu banyak stok meskipun permintaan Pelanggan sedang mengalami penurunan sehingga mengalami kerugian, Sehingga Roemah Donat Lezat selalu menghadapi kesulitan dan kebingungan dalam memperkirakan persediaan stok di bulan berikutnya. Solusi dari permasalahan tersebut yaitu dengan memanfaatkan perhitungan peramalan komparasi metode, kita dapat memperoleh pemahaman yang lebih mendalam dan rinci mengenai kelebihan, kekurangan, serta kinerja relatif dari dua metode yang digunakan untuk mencapai suatu tujuan atau menyelesaikan masalah. Metode yang dibandingkan adalah Single Exponential Smoothing dan Single Moving Average.Kata kunci: single exponential smoothing-single moving average; peramalan; roemah donat lezat; bahan baku; persediaan